The prognostic role of Charlson comorbidity index for critically ill elderly patients - Yıldız, Abdulkerim; Yiğt, Ali; Benli, Ali Ramazan (The European Research Journal, 2020)
Objectives: Comorbidities represent a risk factor for adverse events in several critical illnesses. The aim of this study was to identify the relationship between the Charlson Comorbidity Index (CCI) with mortality and length of stay (LOS) in critically ill elderly patients. Methods: A retrospective analysis was made of patients admitted to our tertiary adult intensive care unit (ICU) between January 2015 and January 2016. The impact of comorbidity was evaluated with the CCI. Other required data were retrieved from the patients’ follow-up records. Results: The study included a total of 251 patients. The mean age was 78.79 ± 6.70 years. The total mortality rate was 41.0%. The most common cause for admission was sepsis and acute respiratory failure (18.3% vs 18.3%). The median APACHE II score was significantly higher in non-survivors than survivors (31.0 [13.0-47.0] vs 21.0 [9.0-40.0]; p < 0.01). The median CCI was 2.0 (0.0-7.0) for survivors and 3.0 (1.0-10.0) for non-survivors. The CCI of non-survivors was significantly higher than that of survivors (p = 0.005). Patients with CCI > 3 had higher mortality than those with CCI ≤ 3 (p < 0.05). The odds ratio of the APACHE II score for mortality was 1.214 (95% CI: 1.154-1.276), and for CCI it was 1.320 (95% CI: 1.088-1.602). There was a significant positive correlation between CCI and LOS (r=0.147; p = 0.020). Conclusions: CCI is strongly associated with both mortality and LOS. It can be used as a prognostic marker for elderly patients in critical care.